Flat midsubstance of the anterior cruciate ligament with tibial "C"-shaped insertion site - Siebold, Rainer; Schuhmacher, Peter; Kirsch, Joachim (Knee surgery, sports traumatology, arthroscopy, 2015)
This anatomical cadaver study was performed to investigate the flat appearance of the midsubstance shape of the anterior cruciate ligament (ACL) and its tibial “C”-shaped insertion site.
Published online: 20 May 2014
Gesehen am 07.05.2020